Raízes que sustentam: narrativas de transição capilar e identidades de mulheres negras – da violação à efetivação de direitos - Eugênia, Sara França (2021)
In the manuscript now presented there are more reflections on roots2 than on hair. Even so, it was from a study on the processes of hair transition and hair it self, in addition to their physicality, that an analysis of the body and how the oppressions of structural racism impact the identity construction of black women was carried out. The hair was analyzed as a diacritical sign that can be perceived as a mark of blackness. Therefore, it is an element capable of influencing the identity process. Curly hair and straight hair have been studied in addition to their physical compositions, seeking to understand their meanings, the effects on the identities of black women and situations in which autonomy over curly or straight hair aesthetics indicates violation or enforcement of rights. Through the analysis of the narratives acquired in the focus groups, we sought to identify, understand and describe the effects of the hair transition, that is, the process of change about individual and subjective perceptions about hair, in the construction of black women's identities. The narratives about curly hair can vary, depending on its subjectivity, but they contribute to the perception of how curly hair, as part of a black body, can become an object of shame, hatred, dissatisfaction and repression due to racism. The meanings given by each woman to her natural hair can change during a hair transition, positively or negatively impacting her self-esteem and producing effects on her identity construction.